Strengthening Jordan’s Family Planning System: Evidence-Based Insights and Adapted Global Best Practices to Improve Modern Contraceptive Uptake - Vuckovic, Myriam; Majali, Sawsan; Khater, Raja; Luiz, Peyton (Archives of Community Medicine and Public Health, 2025)
Background: Jordan’s fertility decline has stalled after decades of progress, and contraceptive use has only very recently recovered from a drop in the 2010s. Between 1990 and 2010, the contraceptive prevalence rate (CPR) rose significantly, contributing to a decline in fertility from 7.1 to 3.3 children per woman. However, from 2012 to 2018, the CPR fell from 61% to 52% and has only recently rebounded to 60%. During this period, many couples turned to less effective methods, such as withdrawal, and the use of modern techniques, including IUDs, pills, injectables, and implants, declined. Reported reasons for non-use include fear of side effects, husband opposition, and lack of awareness. Methods: This narrative review synthesizes existing literature on family planning (FP) in Jordan and identifies global best practices with potential for adaptation in the Jordanian context. It applies a gender-sensitive, evidence-based framework. Results: The review finds that discontinuation of modern methods is high, unmet need rose during the COVID-19 pandemic, and provider attitudes and insufficient male involvement constrain voluntary, rights-based FP. It also highlights the need for improved sexual and reproductive health and rights (SRHR) education, both in schools and through community engagement, to strengthen contraceptive literacy and decision-making. Recommendations span four thematic areas: provider behavior change, male engagement, comprehensive SRHR education, and service delivery. Conclusion: These interventions, grounded in global evidence and contextualized for Jordan, offer implementers actionable guidance. The paper also identifies critical research gaps in contraceptive use, access, and quality of care.